STUDY LITERATURE REVIEW : TEORI SOSIAL FENOMENOLOGI DALAM RISET AKUNTANSI - Timothy Tanujaya; Carmel Meiden (Bajang Institute, 2024)
This research purpose to review the social theory literature, especially phenomenological theory. This research use the Systematic Literature Review (SLR) research method. To collect research data, the